An Analysis of Induction Motor Based on Field Oriented Control with Modulation Techniques Carrier Based Pulse Width Modulation (CBPWM): : - jati, I Ketut Wirya (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2022)
Induction motors have the advantage of simple construction and lower prices. Induction motors have a weakness, namely that they are still coupling, where the interdependence of torque and flux at low speeds regulates the speed more complicated and cannot maintain a constant speed when there is a change in load. To keep the speed of the induction motor can be controlled properly, a method is needed, namely an induction motor using CBPWM with Vector Control. CBPWM can affect the speed of the induction motor, when the Modulation Index is 0.1 the motor speed is 75.03 Rpm and when the Modulation Index 1 the motor speed has an increase of 750 Rpm. From a series of simulations by setting the Modulation Index, as in m=1 it has a speed of 750 Rpm, Maximum Torque 12.1 Nm, Rise Time 0.28s, Settling Time 0.45s, Peak Time 0.93s, and Overshoot 0.01% . Then, the lowest THDi was found at the Modulation Index 1.0 at 1.21% and the lowest THDv was at the Modulation Index 1.1 at 64.91%.